PERAN INTERNATIONAL NON-GOVERNMENT FORUM ON INDONESIAN DEVELOPMENT (INFID) DALAM MENANGKAL RADIKALISME DI INDONESIA - Silaen, Veronika Lestary; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Human rights, democracy and the state are conceptions that need to go hand in hand and support each other. Unresolved gross human rights cases raise many questions about how the Indonesian government is actually trying to reduce the number of violence and deprivation of freedom, especially of religion. The problems experienced by the state are complex and require collaboration from all parties, one of which is international organizations. In an effort to minimize cases of human rights violations and democracy in Indonesia, INFID as an international organization has made various efforts. This research uses qualitative research methodology by conducting centralized interview techniques as primary data and library research as secondary data. This research is descriptive-explanatory which is general to specific. This research uses the international organization theory of David Lewis and Nazneen Kanji with indicators are: 1). Implementer; 2). Catalyst; 3). Partner. The efforts made by INFID include creating a Human Rights and Democracy Program with many derivative programs such as the Human Rights Festival, the Preventing Violent-Extrimism (PVE) Program, and building international cooperation in Human Rights City / District activities to help the pace of good practices in domestic implementation. Keywords: Democracy, Human Rights, INFID, Role of International Organizations